Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am having difficulty with the following problem.

A man covers a distance on a scooter. Had he moved 3Kmph faster he would have taken 40 min less. If he had moved 2kmph slower he would have taken 40 min more. What is the distance (Ans=40)?

Here is what i came up with

$s = (v+3)(t - 40/60)$

$s = (v-2)(t+ 40/60)$

3 variables, two equations? Any suggestions what else I am missing or an easier way to solve this ?

share|cite|improve this question
what about $s=v t$? – Julian Jun 30 '12 at 14:12
up vote 1 down vote accepted

You have $s=v t$. So since $0=-\frac{4}{6}(v+3)+3t=\frac{4}{6}(v-2)-2t$ it follows that $t=\frac{10}{3}$, $v=12$, $s=40$

share|cite|improve this answer
How did you get 4/6 ? – Rajeshwar Jun 30 '12 at 14:36
Could you explain your answer in a little detail – Rajeshwar Jun 30 '12 at 14:36
+1: @Rajeshwar, see my answer for more details. – Cameron Buie Jun 30 '12 at 15:06

Recall also that he actually traveled the distance $s$ at velocity $v$ in time $t$, so we have $s=vt$ as our first equation. Rewriting the other two equations slightly, by distributing (FOIL) and by simplifying the fraction $\frac{40}{60}=\frac{2}{3}$, we have $$\left\{\begin{array}{l}s=vt\\s=vt-\frac{2}{3}v+3t-2\\s=vt+\frac{2}{3}v-2t-\frac{4}{3}\end{array}\right.$$

We readily see (by subtracting the first equation from the other two) that $$\left\{\begin{array}{l}0=-\frac{2}{3}v+3t-2\\0=\frac{2}{3}v-2t-\frac{4}{3}\end{array}\right.$$ and adding those two equations together, we find that $0=t-\frac{10}{3}$, so $t=\frac{10}{3}$. Plugging that back into the first equation in the second system yields $0=-\frac{2}{3}v+10-2$, so $\frac{2}{3}v=8$, so $v=12$. Finally, since $s=vt$, we have $s=12\cdot\frac{10}{3}=40$.

I only posted to expand on Julian's answer! He likely assumed that you could then solve the system of three linear equations in three variables, and so glossed over the details. Feel free to upvote my answer, if it's helpful, but you should arguably accept his over mine.

share|cite|improve this answer
Thank you for specifying the detail. – Rajeshwar Jun 30 '12 at 15:48

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.